The Effect of Multi Level Marketing Information System and Product Quality on Member Performance: Pengaruh Sistem Informasi Multi Level Marketing (MLM) dan Kualitas Produk terhadap Kinerja Member - Mulia Wanto; Lido Sabda Lesmana (Perkumpulan Doktor Indonesia Maju, 2020)
Human resources are a valuable asset in the company, the Information System Multi Level Marketing (MLM) and good product quality will improve performance Member. This study aims to prove that the effect of the partial and simultaneous variable Information System Multi Level Marketing (MLM) (X1) and Product Quality (X2) to the Member-performance variable (Y) on PT Melia Sehat Sejahtera in Batam. The analysis used in this research is multiple linear regression analysis that has the objective to determine the magnitude of the regression coefficients which will show the level of influence of independent variables on the dependent variable. T test results showed that the variable Information System Multi Level Marketing (MLM) (X1) significantly affects the performance Member (Y) and Product Quality variable (X2) significantly affects the performance Member (Y). The test results show that F Information System Multi Level Marketing (MLM) (X1) and Product Quality (X2) the simultaneous effect against Member Performance (Y).